Biodegradation of Iso-valeric Acid in Relation to Other Chemical Indexes and Spatial Liner Risk Assessment at Landfill Topographies - Mid Auchencarroch Experimental Site - C. KOLIOPOULOS, TELEMACHUS; GEORGIA KOLIOPOULOU, M.D. (Asian Journal of Chemistry, 2010)
This paper analyses the effects of different waste management techniques and waste pretreatment on iso-valeric acid emissions and landfill mass biodegradation stages. The biodegradation of Mid Auchencarroch experimental landfill project is studied in 4 different cells. The variations of the examining experimental landfill chemical emissions and their spatial behaviour are presented and analyzed in order to take the right measures in time. The experimental Mid Auchencarroch's data confirm that leachate recirculation, waste pretreatment and co-disposal with inert material are sustainable, accelerating the waste biodegradation. An analysis is made for proper landfills' spatial monitoring and functional support measures so as to avoid any associated landfill emissions' risks and threats to public health.